Perceived Fatality Prior to COVID-19 Infection in 13 Latin American Countries (FAT-LAT-COVID-19): Revalidation of a Shortened Scale - Mejia, Christian R.; Aveiro-Róbalo, Telmo Raúl; Garlisi-Torales, Luciana D.; Carranza Esteban, Renzo Felipe; Mamani-Benito, Oscar; Vilela-Estrada, Martín A.; Serna-Alarcón, Víctor; Jaramillo-Aguilar, Damary S.; Rojas-Roa, Javiera L. (Frontiers in Psychiatry, 2022)
Background: COVID-19 has generated a great repercussion in the population at a global level, that is why it is important to measure the fatalistic ideas of those who have not yet been infected. The aim of this article is Revalidate a scale that measures the fatalistic perception prior to COVID-19 infection in a population of 13 Latin American countries. Method: An instrumental study was carried out, a first validated scale was taken in Peru, with seven items divided into two factors and with five possible Likert-type responses (from strongly disagreeing to strongly agreeing). The one that was submitted to a large population in 13 Spanish-speaking countries in Latin America; For each of the 7 questions, 886 people were surveyed. With these results, descriptive and analytical statistics were performed. Results: The mean, standard deviation, skewness and kurtosis of the seven primary questions were adequate in most cases. In the confirmatory factor analysis, the lack of adjustment with the index modification technique was improved, thus ruling out the items 1 and 6; with this, satisfactory goodness of fit indices were obtained (CFI = 0.972, TLI = 0.931, GFI = 0.990, AGFI = 0.961, RMSEA = 0.080 and RMR = 0.047). Therefore, the final 2-factor structure had a fairly adequate Cronbach's Alpha (0.72, with a 95% confidence interval = 0.70 - 0.73). Conclusion: The scale that allows measuring the fatalism of Latin American countries in the face of the pandemic generated by COVID-19 was revalidated and reduced.